2022
DOI: 10.14202/vetworld.2022.565-589
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and natural infections of severe acute respiratory syndrome-related coronavirus 2 in pets and wild and farm animals

Abstract: The severe acute respiratory syndrome-related coronavirus 2 (SARS-CoV-2) has spread globally and has led to extremely high mortality rates. In addition to infecting humans, this virus also has infected animals. Experimental studies and natural infections showed that dogs have a low susceptibility to SARS-CoV-2 infection, whereas domesticated cats and other animals in the family Felidae, such as lions, tigers, snow leopards, and cougars, have a high susceptibility to viral infections. In addition, wild white-ta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 115 publications
0
15
0
Order By: Relevance
“…The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) causing coronavirus disease-2019 (COVID-19) is a betacoronavirus (β-CoV) closely related to Severe Acute Respiratory Syndrome (SARS-CoV) and the Middle East Respiratory Syndrome Coronavirus (MERS-CoV), which have also caused severe outbreaks in human populations. Human-to-animal transmission events during the COVID-19 pandemic have been documented in several countries, including Hong Kong, Belgium, the United States, Netherlands, Denmark, Spain, Germany, and France, among others [ 1 , 2 ]. Furthermore, several animal species have proven to be susceptible to SARS-CoV-2 infection, both naturally and experimentally [ 2 , 3 ], including mustelids such as farmed American mink ( Neogale vison ) [ 4 , 5 ], mink and ferret under experimental conditions [ 6 , 7 , 8 , 9 , 10 ], household and kept ferrets [ 11 , 12 ], captive Asian small-clawed otters [ 13 ], wild Eurasian river otter ( Lutra lutra ) [ 14 ] and feral American mink [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) causing coronavirus disease-2019 (COVID-19) is a betacoronavirus (β-CoV) closely related to Severe Acute Respiratory Syndrome (SARS-CoV) and the Middle East Respiratory Syndrome Coronavirus (MERS-CoV), which have also caused severe outbreaks in human populations. Human-to-animal transmission events during the COVID-19 pandemic have been documented in several countries, including Hong Kong, Belgium, the United States, Netherlands, Denmark, Spain, Germany, and France, among others [ 1 , 2 ]. Furthermore, several animal species have proven to be susceptible to SARS-CoV-2 infection, both naturally and experimentally [ 2 , 3 ], including mustelids such as farmed American mink ( Neogale vison ) [ 4 , 5 ], mink and ferret under experimental conditions [ 6 , 7 , 8 , 9 , 10 ], household and kept ferrets [ 11 , 12 ], captive Asian small-clawed otters [ 13 ], wild Eurasian river otter ( Lutra lutra ) [ 14 ] and feral American mink [ 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%
“…Human-to-animal transmission events during the COVID-19 pandemic have been documented in several countries, including Hong Kong, Belgium, the United States, Netherlands, Denmark, Spain, Germany, and France, among others [ 1 , 2 ]. Furthermore, several animal species have proven to be susceptible to SARS-CoV-2 infection, both naturally and experimentally [ 2 , 3 ], including mustelids such as farmed American mink ( Neogale vison ) [ 4 , 5 ], mink and ferret under experimental conditions [ 6 , 7 , 8 , 9 , 10 ], household and kept ferrets [ 11 , 12 ], captive Asian small-clawed otters [ 13 ], wild Eurasian river otter ( Lutra lutra ) [ 14 ] and feral American mink [ 15 , 16 ]. In this sense, the virus spreads efficiently in farmed American mink.…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of animal species are susceptible to SARS-CoV-2 natural infections (ferret, cat, dog, mink, tiger, lion, gorilla, puma, and snow leopard) ( 3 5 ). However, genetic and epidemiological studies have suggested that these infections were introduced from humans rather than enzootic virus circulation (WHO-convened Global Study of Origins of SARS-CoV-2: China Part OMS).…”
Section: Introductionmentioning
confidence: 99%
“…However, genetic and epidemiological studies have suggested that these infections were introduced from humans rather than enzootic virus circulation (WHO-convened Global Study of Origins of SARS-CoV-2: China Part OMS). Experimental infections have also demonstrated the susceptibility of several animals to SARS-CoV-2 infection, mainly cats, ferrets, hamsters, and deer, as well as a certain resistance to infection by other species (cattle, pigs, chickens) ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has caused a global pandemic of the disease known as coronavirus disease 2019 . A wide range of species of domestic animals and wildlife have been infected by SARS-CoV-2 (1)(2)(3)(4). Humans who handle horses have considerable direct contact with horses, including proximity to mucosal surfaces of the mouth and nose during activities such as haltering, placing bits, and feeding.…”
Section: Introductionmentioning
confidence: 99%